2016
DOI: 10.5114/aoms.2016.57582
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes are associated with tracheal structural abnormalities in patients with acromegaly

Abstract: IntroductionAlthough impaired pulmonary function and respiratory sleep disorders are described as responsible for increased mortality in acromegalic patients, little is known about the tracheal abnormalities in this group of patients. Thus, the objectives of this study were to describe the tracheal structural abnormalities and correlate these changes with the respiratory function and clinical data of acromegalic patients.Material and methodsThis is a cross-sectional study that was carried out at two university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A positive and strong correlation was also noted between the FEF 50% /FIF 50% ratio and the Δ tracheal diameters obtained through inspiratory CT but not through expiratory CT. This finding may be explained by the tendency towards tracheal collapse deriving from the development of negative intraluminal pressure during inspiration, which disappears during expiration, when the direction of transmural pressure, with the subsequent opening of the airways, is inverted …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A positive and strong correlation was also noted between the FEF 50% /FIF 50% ratio and the Δ tracheal diameters obtained through inspiratory CT but not through expiratory CT. This finding may be explained by the tendency towards tracheal collapse deriving from the development of negative intraluminal pressure during inspiration, which disappears during expiration, when the direction of transmural pressure, with the subsequent opening of the airways, is inverted …”
Section: Discussionmentioning
confidence: 99%
“…29 We found that patients with acromegaly show higher values of the FEF 50% /FIF 50% ratio than control subjects. 4,23,26 In the flow-volume loop obtained through spirometry, an increased FEF 50% /FIF 50% ratio has been used as an extrathoracic large airway obstruction (LAO) marker, as there is limitation of the airflow during inspiration in the presence of narrowed airways due to the propagation of negative intraluminal pressure in this portion of the airway. 4 In this study, this finding was corroborated by the higher SI based on airway lumen volumetry measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations